FORMATION AND DEVELOPMENT OF INTEGRATED TEACHING IN PRIMARY EDUCATION (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
this article presents an understanding of the process of primary education, information on the formation and development of integrated teaching in primary education.